15(2X+3)+97=110-5X

Simple and best practice solution for 15(2X+3)+97=110-5X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15(2X+3)+97=110-5X equation:


Simplifying
15(2X + 3) + 97 = 110 + -5X

Reorder the terms:
15(3 + 2X) + 97 = 110 + -5X
(3 * 15 + 2X * 15) + 97 = 110 + -5X
(45 + 30X) + 97 = 110 + -5X

Reorder the terms:
45 + 97 + 30X = 110 + -5X

Combine like terms: 45 + 97 = 142
142 + 30X = 110 + -5X

Solving
142 + 30X = 110 + -5X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '5X' to each side of the equation.
142 + 30X + 5X = 110 + -5X + 5X

Combine like terms: 30X + 5X = 35X
142 + 35X = 110 + -5X + 5X

Combine like terms: -5X + 5X = 0
142 + 35X = 110 + 0
142 + 35X = 110

Add '-142' to each side of the equation.
142 + -142 + 35X = 110 + -142

Combine like terms: 142 + -142 = 0
0 + 35X = 110 + -142
35X = 110 + -142

Combine like terms: 110 + -142 = -32
35X = -32

Divide each side by '35'.
X = -0.9142857143

Simplifying
X = -0.9142857143

See similar equations:

| -7(20y)= | | 2{2x+3}=-3{x+5} | | 6{k-2}=3k-6 | | -x-4-3x=-2x-3-1 | | 8=-4x | | 2(6y)= | | -53=x-41 | | -8=1-y/(-2)-0 | | 15(2x+3)=13-5x | | -(20.5-17.9)+(5.2-3.7)= | | 2d-(-4)=8 | | 14b-6=2b+8 | | 3(x+5)+2=17 | | 0.5x+3=9 | | 7x-2(3x-9)=28 | | 14=8-(-2k) | | 14=8-(2k) | | 7y-24y-5=80 | | 4x-6(-4x+2)=240 | | h-5=-6/7 | | 82=10x-2x | | z^2=-8z | | 10(33)-7=2(13+5(33)) | | 2x+y=10x-1 | | 75=3(-10-3)+6t | | 2465367x/26x/6=0 | | 2*(13*5)=(2*5)*13 | | 3px=2q(r-5x) | | y(y+4)=0 | | 2x+3x=3578 | | 3k+5=7 | | 6k(5k-8)= |

Equations solver categories